Science fact vs science fiction: A ChatGPT immunological review experiment gone awry - Wittmann, Jürgen (Immunology letters, 2023)
Artificial intelligence (AI) has made great progress in recent years. The latest chatbot to make a splash is ChatGPT. To see if this type of AI could also be helpful in creating an immunological review article, I put a planned review on different classes of small RNAs during murine B cell development to the test. Although the general wording sounded very polished and convincing, ChatGPT encountered great difficulties when asked for details and references and made many incorrect statements, leading me to conclude that this kind of AI is not (yet?) suitable for assisting in the writing of scientific articles.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Chatbot; ChatGPT; Human intervention; Manuscript preparation; MicroRNAs; References